2017
DOI: 10.31351/vol23iss2pp13-23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Clinical use of Metformin or Pioglitazone in Combination with Meloxicam in Patients with Knee Osteoarthritis; using Knee Injury and Osteoarthritis outcome Score

Abstract: Osteoarthritis is the most prevalent arthritic disease and a leading cause of disability. The pathogenesis of osteoarthritis involves multiple etiologies, including variable degree of synovial inflammation. Metformin and pioglitazone could potentially reduce the levels and activity of inflammatory mediators. This may consider as a new therapeutic approach added to the current used drugs in an attempt to decrease the pain, inflammation, and improve daily activity and quality of life in patients with knee osteoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The results of another clinical trial in OA patients confirm the beneficial effects of metformin such as changes in western Ontario and McMaster universities osteoarthritis index (WOMAC) score and visual analog scale (VAS) knee pain with a maximum dose of 2 g/day for 24 months [ 71 ]. In another study, the results showed that metformin (1000 mg/day for 12 weeks) in combination with meloxicam (15 mg/day) significantly improved KOOS components compared to the setting that meloxicam was used alone in OA patients [ 72 ]. Recently, some studies have reported the therapeutic influence of metformin on reducing cartilage degeneration and joint pain in animal models and cohort studies [ 73 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of another clinical trial in OA patients confirm the beneficial effects of metformin such as changes in western Ontario and McMaster universities osteoarthritis index (WOMAC) score and visual analog scale (VAS) knee pain with a maximum dose of 2 g/day for 24 months [ 71 ]. In another study, the results showed that metformin (1000 mg/day for 12 weeks) in combination with meloxicam (15 mg/day) significantly improved KOOS components compared to the setting that meloxicam was used alone in OA patients [ 72 ]. Recently, some studies have reported the therapeutic influence of metformin on reducing cartilage degeneration and joint pain in animal models and cohort studies [ 73 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, in addition to chondroprotective and anti-inflammatory effects, metformin was shown to be able to improve pain, such that rats or mice treated with metformin showed increased paw withdraw latency indicative of reduction in pain 13 15 16 35. In human studies, a randomised, double-blind trial showed that the combination of metformin with meloxicam improved knee pain by at least 50% more than meloxicam alone 36. Additionally, one of the metformin’s pleiotropic effects is mild weight loss (~2.5%),37 which is important when tackling the slow insidious weight creep from early to middle adulthood,38–40 particularly when obesity is a well-known risk factor for OA, and for more symptomatic and more progressive knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial in patients with symptomatic, radiologically confirmed knee OA, a greater reduction in serum levels of IL-1β, IL-8, and TNF-α was found in patients treated with metformin and meloxicam compared to those receiving meloxicam alone over a 12-week period [ 71 ]. In patients with OA and type II diabetes mellitus, the combined administration of a COX-2 inhibitor and metformin resulted in a reduced incidence of joint replacement compared with patients receiving a COX-2 inhibitor alone during a 10-year period of follow-up [ 72 ].…”
Section: Pleiotropic Effects Of Metformin In Osteoarthritismentioning
confidence: 99%